Balanced Nutrition and Crop Production Practices for Closing Sorghum Yield Gaps - B. McHenry; Eric Adee; J. Kimball; P. V. Vara Prasad; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2016)
In order to study how diverse cropping system approaches influence grain sorghum productivity, field experiments were conducted in Topeka, KS at the Kansas River Valley Experiment Field; and in Ottawa, KS at the East Central Kansas Experiment Field. The primary objective of this study was to understand how to close yield gaps between the current on-farm yields and the maximum attainable yields. The factors that were tested include narrow row spacing; high and low plant population; balanced nutrition practices, including various timings of nitrogen, phosphorus, and potassium (N-P-K); micronutrient applications of iron and zinc (Fe and Zn); crop protection with fungicide and insecticide applications; plant growth regulator effects; and the use of precision agricultural technology for maximizing yields, including a GreenSeeker meter (Trimble Navigation, Westminster, CO) for more precisely determining N needs for sorghum. Grain sorghum yields ranged from 149 to 166 bu/a in Topeka, KS under irrigation, and from 78 to 100 bu/a in Ottawa, KS, under dryland conditions. At Ottawa, yield potential was limited by precipitation, 10.8 inch. Still, sorghum yield gap between the highest (treatment #2, “kitchen sink” but with low seeding rate) and lowest (treatment #10, “standard practice”) was 22 bushels per acre. The production practices that produced the highest yields varied between the two locations.
Keywords: Sorghum; nutrient uptake; production practices